IMPLEMENTATION OF ENVIRONMENTAL EDUCATION AND IMPACT STUDENT'S ENVIRONMENTAL CARE ATTITUDE TO ADIWIYATA SCHOOL - Karma Iswasta Eka; Suwarno Suwarno (Jurnal Muara Pendidikan, 2020)
Character is an act of person based on attitudes and behavior. Simon in Mu’in (2011: 160) says that character is a collection of values ​​that lead to a system, which underlies the thoughts, attitudes, and behaviors displayed. A person's character greatly influences actions and behavior in daily life. One of the characters who want to be formed in elementary schools is environmental care. Environmental care can be formed through a variety of ways, one of which is through Adiwiyata schools. The purpose of this study was to obtain a picture of the impact of Adiwiyata School on the students' environmental care character. The study location was at Adiwiyata School, SDN 2 Sokaraja Kulon and SD Locondong. The retrieval of data through non-participant observation, semi-structured interviews, and scrutinizing documents and observations of research objects.The research instrument is the researcher himself. The results showed that 1) the school environment is still showing as an Adiwiyata school which was achieved a few years ago, 2) planting an attitude of caring for the environment is done through academic and non-academic activities, 3) The character of the environmental care attitude of students is well formed through academic and non-academic activities.